1998
DOI: 10.1902/jop.1998.69.12.1373
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Utility of Specific Microbiological Markers for Periodontal Diseases

Abstract: National efforts directed toward improving our understanding of the epidemiology of periodontal disease began nearly a half century ago following the development of Russell's periodontal index (PI). United States Public Health Service agencies began national surveillance activities for periodontal disease with the first National Health Examination Survey in 1960 to 1962, and this continued periodically through 2004 in the National Health and Nutrition Examination Survey (NHANES). Periodontal disease status was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Sites that demonstrate progressive attachment loss in established adult periodontitis have been associated with the increased prevalence of several Gram‐negative species, including A. actinomycetemcomitans , B. forsythus , C. rectus , Eubacterium timidum , Fusobacterium nucleatum , Peptostreptococcus micros , P. gingivalis , Prevotella intermedia and Treponema denticola (7–11). The association of microorganisms with specific periodontal diseases, as well as with disease progression, has led to the suggestion that subgingival species could be used as diagnostic markers (12). However, the emergence or increased prevalence of a specific bacterial species at a given site has, in itself, proven insufficient to predict subsequent disease progression, as many individuals in longitudinal studies exhibit infection without experiencing attachment loss.…”
mentioning
confidence: 99%
“…Sites that demonstrate progressive attachment loss in established adult periodontitis have been associated with the increased prevalence of several Gram‐negative species, including A. actinomycetemcomitans , B. forsythus , C. rectus , Eubacterium timidum , Fusobacterium nucleatum , Peptostreptococcus micros , P. gingivalis , Prevotella intermedia and Treponema denticola (7–11). The association of microorganisms with specific periodontal diseases, as well as with disease progression, has led to the suggestion that subgingival species could be used as diagnostic markers (12). However, the emergence or increased prevalence of a specific bacterial species at a given site has, in itself, proven insufficient to predict subsequent disease progression, as many individuals in longitudinal studies exhibit infection without experiencing attachment loss.…”
mentioning
confidence: 99%
“…This implies, that the periodontal condition at present or in time, is described inaccurately by the use of a limited number of diseased sites as a subject level variable. The clinical measurements of small numbers of deep sites have been used as patient level descriptors in numerous studies (Loesche et al 1985, Goené et al 1990, Rams et al 1990, Rodenburg et al 1990, Van Winkelhoff et al 1992, Matisko & Bissada 1993, Pavičić et al 1994, Bollen & Quirynen 1996, Renvert et al 1996, 1998, Winkel et al 1997, Eggert et al 1998a, 1998b, Shiloah et al 1998, Takamatsu et al 1999). Although, in these studies, the measurements have shown changes in time, the magnitude of these changes is not easily translated into a full‐mouth level mean.…”
Section: Discussionmentioning
confidence: 99%
“…Studies evaluating the effect of periodontal therapy both clinically and microbiologically have used the mean of the deepest site per quadrant (4‐sites) to describe the patient's response (Loesche et al 1985, Rams et al 1990, Goené et al 1990, Rodenburg et al 1990, Van Winkelhoff et al 1992, Pavičić et al 1994, Winkel et al 1997, Shiloah et al 1998, Takamatsu et al 1999). The mean of a small number of deep sites as the only patient level variable is also frequently used (Matisko & Bissada 1993, Bollen & Quirynen 1996, Renvert et al 1996, 1998, Eggert et al 1998a, 1998b). However, the question arises whether 4 deep sites, i.e.…”
mentioning
confidence: 99%
“…For cases at risk of more severe attachment loss, additional diagnostic tests are recommended (Chapple 1997). To help clinicians with periodontal decision making, several measures have been introduced (Holtzman & Kornman 1992, McGuire & Newman 1995, Newman 1996, Wilson & Kornman 1996, Eggert et al 1998, Wennström et al 1990, Wennström 1998). Despite the measures available and the recommendations of the CR, clinicians' treatment decisions frequently vary depending on the patient and the desired level of clinical outcome, as discussed by Matthews (1994), Bellamy et al (1996), and Greenstein (1997).…”
mentioning
confidence: 99%